Analisis hermeneutik sahiron pada fenomena flexing: Studi pendekatan Mā’nā Cum Maghzā dalam surah At-Takatsur - Salamah, Ika Hilmiatus (Maliki Interdisciplinary Journal, 2024)
The activity of showing off wealth on social media is very common among today's society. This activity is usually called flexing behavior. People who have a flexing lifestyle do not care about the wealth they get, the position and descendants they get. However, they only care about how other people view them as having something luxurious. This research is in the form of a literature review using a descriptive approach with Ma'na Cum Maghza as its analytical tool. The data source in this study is the At-Takatsur surah, while the secondary data source uses journal articles that are relevant to the theme. The results of this study reveal that the at-Takatsur surah is closely related to its asbabun nuzul and in the current context is relevant to flexing behavior, which is an act that when done intentionally or unintentionally will still get sin.